2012
DOI: 10.1016/j.compstruct.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

A design model for fibre reinforced concrete beams pre-stressed with steel and FRP bars

Abstract: This paper presents a design oriented model to determine the moment-curvature relationship of elements of rectangular cross section failing in bending, made by strain softening or strain hardening fibre reinforced concrete (FRC) and reinforced with perfectly bonded pre-stressed steel and fibre reinforced polymeric (FRP) bars. Since FRP bars are not affected by corrosion, they have the minimum FRC cover thickness that guaranty proper bond conditions, while steel bars are positioned with a thicker FRC cover to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Previous work [9] shown that, using a cross section layered model that takes into account the constitutive laws of the intervening materials, and the kinematic and the equilibrium conditions, the deformational behavior of structural elements failing in bending can be predicted from the momentecurvature relation, Mec, of the representative cross sections of these elements, using the algorithm described elsewhere [26,27].…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Previous work [9] shown that, using a cross section layered model that takes into account the constitutive laws of the intervening materials, and the kinematic and the equilibrium conditions, the deformational behavior of structural elements failing in bending can be predicted from the momentecurvature relation, Mec, of the representative cross sections of these elements, using the algorithm described elsewhere [26,27].…”
Section: Numerical Simulationmentioning
confidence: 99%
“…By applying the principle of virtual work, the mid-span deflection of the beam for the kth loading step d k ð Þ is obtained, resulting a P k À d k point of the force-deflection response of the beam [29].…”
Section: Evaluation Of Force-deflection Relationshipmentioning
confidence: 99%
“…Numerical approach to determine the force-deflection response of statically determinate beams failing in bending[29].…”
mentioning
confidence: 99%
“…Previous work [10] shows that, using a cross section layered model that takes into account the constitutive laws of the intervening materials, and the kinematic and the equilibrium conditions, the deformational behavior of structural elements failing in bending can be predicted from the moment-curvature relation, M-χ, of the representative cross sections of these elements, using the algorithm described elsewhere [23,24].…”
Section: Numerical Simulationmentioning
confidence: 99%